The role of isolated farmsteads in the open landscape protection on the example of Kashubia - Górka, Anna (Rola zagród samotniczych w ochronie krajobrazu otwartego na przykładzie Kaszub, 2023)
As a result of the social and economic transformation of rural areas, open landscapes are disappearing. Former farmsteads are being devastated or beginning to lose their landscape context due to the spread of residential building development. At the same time, in many places, the farmstead form is clearly legible and remains an element with which the view is structured and enriched. The article was aimed at drawing attention to the multidimensional importance of isolated farmsteads and the need to recognise their surviving resources. Being distinguishing features with which the attractiveness of an open landscape can be determined, they inspire the development of a multifunctional rural economy led by the local community. Isolated farmsteads can respond to the city’s problems and function in many non-agricultural areas, including education, tourism and recreation, nature protection and health protection. Protection of the building development of former farmsteads may provide a tool to effectively support the shaping of spatial order in large areas. The article presents a method for describing the preservation condition of single-manor buildings developed at the turn of the 19th and 20th centuries. It is proposed that the study analyses the architectural features of farmsteads that play an important part in the recognition of such building development in the open landscape. Observation areas were selected based on the results of remote identification of the location of historic farmsteads and buildings. The field study was conducted in the central part of Kashubia, along selected scenic routes. These routes comprised 26 solitary homesteads. In half of the cases studied, the exposure of the farmstead buildings deteriorated due to the proximity of modern residential building development. The spatial layout of the majority of farmsteads has changed, which most commonly resulted from expansion beyond the former outline of the farmyard. Numerous historic buildings have been rebuilt. Despite the above-mentioned modifications, in the study area, the farmstead has remained a distinctive feature of the landscape and retained the potential for transformation to be used in the sustainable development economy. The results encourage the study to be continued. The identified resources and architectural values of the traditional farmstead could support the management and protection of the heritage of agricultural landscapes.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 49-59
Keywords: architektura; farmsteads; open landscape; heritage protection; sustainable rural development; Kashubia; zagrody; krajobraz otwarty; ochrona dziedzictwa; zrównoważony rozwój wsi; Kaszuby